Pre 'ibadah camp propositions on humanizing education with brotherhood and unity - Mhd. Sarif, Suhaimi (Kulliyyah of Economics and Management Sciences IIUM, 2022)
In Chapter 1, Nur Arfifah Abdul Sabian provides the overview of the 'ibadah camp for 2022. In Chapter 2, Azniza Hartini contemplates on the reality of unity and altruism in light of the amount of time spent with family during these phases of teaching. Arbaiah Abdul Razak related to her experience that she was struggling and learning to cope with altruism in Chapter 3. She found out that altruism is in fact a form of sunnah and 'ibadah, and the religion of Islam represents the most perfect expression of altruism. Chapter 4, Fadhilah Abdullah Asuhaimi and Farhanin Abdullah Asuhaimi reflected the ta'awun concept practised during the Prophet Muhammad صلى الله عليه وسلم period. Yusof Ismail's Chapter 5 reflected that unity may be based on a variety of bases. In Chapter 6, Azura Omar, Indra Fajar Alamsyah and Suhaimi Mhd Sarif emphasized that Ukhuwwah Islamiyyah is a powerful tool to create and sustain unity to form an Islamic community-based enterprises resulting in spiritual, social, and economic changes. Authors Suhaimi Mhd Sarif, Yusof Ismail and Mohammad Fikri Abdul Wahid postulated that love and care tie the bonding in Chapter 7. They described the loving and caring practices in sustaining ukhuwwah Islamiyyah (brotherhood) and wihdah (unity) in the contexts of Muslims in Australia. In Chapter 8, Hamdino Bin Hamdan and Hairul Azlan Annuar argued that the concept of brotherhood and silaturahim practiced in Islamic social entrepreneurship, which in turn leads to the unification of the ummah. Islamic social entrepreneurship activities that are carried out can further strengthen the relationship of silaturahim and brotherhood between Muslims in addition to strengthening the unity of ummah and their economy.